The study on the effect of blade guide strip on aerodynamic performance of horizontal axis wind turbine - Li, Guowen; Song, Haotian; Wu, Xinghui; Sun, Xinhua (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This paper mainly studies the influence of sticking hidden movable airflow guide strips to the surface of horizontal axis wind turbine blades on the aerodynamic performance of the blades. The experimental data suggest that the guide strip changes the direction of the airflow. A reverse force will be generated in the opposite direction of the airflow outflow, i.e. the blade guide strip’s resistance and the airflow’s distance on the blade surface will be increased. The lift of the blade will be increased with a low starting wind speed and a significant wind energy utilization effect. The research results show that the guide strip structure can increase the lift coefficient of the blade by 9.1% under the conditions of a small angle of attack. When the wind speed reaches 8 m/s, the power coefficient increases by 14.1% and the starting wind speed decreases by 0.5 m/s. However, negative resistance of the guide strip was increased at high incoming flow speeds. At this time, the guide strip was adapted to level the actuator and placed on the blade’s surface. The experimental results show that when the guide strip is retracted, the output power of the wind turbine is the same as that of the prototype blade. Therefore, the guide strip blades with retraction and extension functions enhance the low-speed performance of the wind turbine while maintaining its high-speed performance.